Analysis of Factors That Influence The Development of Lecturer Career in YLPTK Optimization Refraction In Padang - Novalinda, Rina; Fajra, Melda; Giatman, M.; Syahril, Syahril (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study is to determine the factors that influence the career development of lecturers. Refraksi Optisi YLPTK Padang lecturer research subjects. This type of correlational quantitative research. Data collection techniques using a questionnaire with a Likert scale. Data analysis techniques with the F test and t test. this research is important to examine factors influencing the career development of lecturers. The results of data analysis showed that work commitment, leadership, colleague support and competence together or partially influenced lecturer career development.